Testing Piketty's Hypothesis on the Drivers of Income Inequality : Evidence from Panel VARs with Heterogeneous Dynamics - Goes, Carlos (IMF Working Papers; Working Paper ;, 2016)
Thomas Piketty's Capital in the Twenty-First Century puts forth a logically consistent explanation for changes in income and wealth inequality patterns. However, while rich in data, the book provides no formal empirical testing for its theoretical causal chain. In this paper, I build a set of Panel SVAR models to check if inequality and capital share in the national income move up as the r-g gap grows. Using a sample of 19 advanced economies spanning over 30 years, I find no empirical evidence that dynamics move in the way Piketty suggests. Results are robust to several alternative estimates of r-g.